The Losing Media? An Empirical Study of Defamation Litigation in China. (10th April 2017) - He, Xin; Lin, Fen
Abstract: Following a well-established research tradition on court decisions, this study analyses 524 defamation cases in China from 1993 to 2013, explores the media's success possibilities, and investigates the role of party capacity, political influence and the medium effect. Contrary to the existing assertions, we find that the media are not necessarily losing. On average, from 1993 to 2013, the success rate of news media in Chinese defamation courts was 42 per cent, and this rate has been increasing since 2005. We also find that government officials and Party organs had consistent advantages in court, while ordinary plaintiffs, magazines and websites had less success. The medium of the media (i.e. print, broadcast, internet) makes a difference, as do the government policies governing the media. In addition, local protectionism exists, but it is less rampant than expected. These findings compel us to rethink the dynamics among the media, the courts and the state, and their implications on China's institutional resilience. 摘要: 延续既有的法庭研究传统, 本文研究 1993 年至 2013 年间 524 起控告媒体的名誉侵权案件, 探讨媒体胜诉概率, 并分析媒体的资源、政治影响和媒介效应对其胜率的影响。与现有看法相反, 我们发现媒体胜率不低。从 1993 年至 2013 年, 新闻媒体在中国名誉侵权案中的平均胜率是 42 %, 且该比率从 2005 年起逐渐提高。在起诉媒体时, 政府官员和党政机关在法庭审判中一直占有优势。而普通原告、杂志和网站则处于相对劣势。不同的媒介 (如报刊、广播、网络) 和政府的媒介管理政策也对媒体的胜诉率产生影响。此外, 在此类案件中, 地方保护主义虽然存在, 但是没有预期中显著。这些实证数据启发我们重新思考媒体、法院和政府之间的动态关系, 及其对中国体制弹性的影响。